2014
DOI: 10.1186/1297-9716-45-59
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the TLR9 ligand CpG-oligodeoxynucleotide on the protective immune response to alcelaphine herpesvirus-1-mediated malignant catarrhal fever in cattle

Abstract: We wished to determine the effect of of CpG ODN adjuvant on the magnitude and duration of protective immunity against alcelaphine herpesvirus-1 (AlHV-1) malignant catarrhal fever (MCF), a fatal lymphoproliferative disease of cattle. Immunity was associated with a mucosal barrier of virus-neutralising antibody. The results showed that CpG ODN included either with emulsigen adjuvant and attenuated AlHV-1 (atAlHV-1) or alone with atAlHV-1 did not affect the overall protection from clinical disease or duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This boosted (anamnestic) response in the infected cattle indicates that the virus managed to infect these animals, stimulating memory cells to produce more antibodies. This was consistent with previous work (Parameswaran et al, 2014, Russell et al, 2012). As 12 of these cattle died, we conclude that, if the vaccine fails to protect against infection, any antibody response that takes place after infection is not protective.…”
Section: Discussionsupporting
confidence: 94%
“…This boosted (anamnestic) response in the infected cattle indicates that the virus managed to infect these animals, stimulating memory cells to produce more antibodies. This was consistent with previous work (Parameswaran et al, 2014, Russell et al, 2012). As 12 of these cattle died, we conclude that, if the vaccine fails to protect against infection, any antibody response that takes place after infection is not protective.…”
Section: Discussionsupporting
confidence: 94%
“…6-month duration of protective immunity in vaccinated animals Recombinant AlHV-1 virus with ORF73 deletion Rabbit 2013 [ 50 ] ORF73-deleted recombinant virus induced a strong antibody response. Animals protected against MCF-associated pathology following lethal challenge and with virulent virus Attenuated C500 strain-AlHV-1 from serially passaged cell cultures with Emulsigen (licensed) adjuvant and unmethylated CpG oligodeoxy nucleotide (TLR9 agonist) Cattle 2014 [ 49 ] Unmethylated CpG oligodeoxynucleotide offers no additional advantage to length or level of protective immunity achieved using attenuated AlHV-1 with Emulsigen (licensed) adjuvant …”
Section: Integrated Control Of Wa-mcf: Current Knowledge and Perspectmentioning
confidence: 99%
“…The antibody titre in protected animals did not rise significantly after challenge suggesting that virus was unable to penetrate the mucosal barrier and boost the response. Conversely, in vaccinated animals that succumbed to MCF, the antibody titre rose significantly after challenge, indicating successful virus entry and stimulation of an anamnestic response that was not protective (Russell et al, 2012;Parameswaran et al, 2014). This study also showed that in a few animals, protection from MCF was found despite the generation of little or no neutralising antibody, suggesting that immune mechanisms other than virus-neutralising antibody may influence protection from AlHV-1 (Parameswaran et al, 2014).…”
Section: Introductionmentioning
confidence: 68%
“…In susceptible species, primary, transient viral replication appears to occur within lung epithelium, after which the virus disseminates systemically . It has been suggested that establishment of a protective mucosal immune barrier in the naso-pharyngeal region is critical for vaccine protection against MCF infection Parameswaran et al, 2014). A recent vaccination study has shown that a high-titre virus-specific antibody response prior to challenge correlates with protection (Russell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation